PERLINDUNGAN HUKUM TERHADAP KREDITOR PEMEGANG JAMINAN FIDUSIA DALAM KEPAILITAN DEBITUR - Andika Wijaya; Hendro Juandra; Buyung Ageng Islami; Pius Pati Molan; Cakra P. Octavianus (Fakultas Hukum Universitas Narotama, 2020)
This study was made to find to find a form of legal protection for Creditors holding fiduciary guarantees in the event that the Debtor is declared bankrupt. Research conducted after the Decision of the Constitutional Court of the Republic of Indonesia Number: 18 / PUU-XVII / 2019 dated January 6, 2020. This decision was carried out in accordance with the fiduciary Guarantee Holder's right to execute objects bound by fiduciary guarantees. This research is a normative juridical study, by statute, conceptual and cases approach. Research contains novelty and original elements, which can be used as a source of reference for Creditors who holding fiduciary guarantees to maximize their right to increase the bankruptcy of the Debtor. Through this research, creditors who receive fiduciary security rights (all financial service institutions both conventional and sharia, such as: banks, finance companies, mortgage companies, etc.) can adjust themselves to bankruptcy procedures without having to violate the provisions of fiduciary guarantee laws that have experienced post-change after Decision of the Constitutional Court of the Republic of Indonesia Number: 18 / PUU-XVII / 2019 dated January 6, 2020.